Effect of storage time on germination of Avocado seeds and seedlings quality. - مخول , جرجس; عطاف, وفاء (Latakia University Journal -Biological Sciences Series, 2020)
The research was carried out in the agricultural nursery of Tishreen University during 2018 and 2019 on seeds of one variety. The results sh0wed that the highest germination percentage was obtained when extracting seeds from the fruits and planting directly without storage. The average of germination rate was 87.50%. - Avocado seed storage affected the germination percentage significantly, as this ratio decreased with prolonging the period of storage in the fridge at a temperature of 5 ° ± 2 ° C, and the lowest germination percentage reached 4.17% in the treatment of seed storage for 60 days before the date of planting. - The tallest plants were in direct cultivation treatment in the center of cultivation and swallowing 51.35 cm as an average for two years, while the length of the plant was 13 cm in storage treatment for a period of 60 days before planting. - The average number of leaves in direct-cultivation plants was 37, whereas this number was only 9 in storage for a period of 60 days. - Our results also showed the effect of storing seeds on the number of plants resulting from a single seed, as the number decreased significantly with the length of the storage period and the average number of plants was 4 in the direct cultivation treatment, whereas it was one plant in the storage treatments for a period of 40 and 60 days.